Parent perspectives on autistic girls' friendships and futures. (August 2018) - Sedgewick, Felicity; Hill, Vivian; Pellicano, Elizabeth
Background and aims: Young people's parents often play a key role in facilitating friendships and have their own views on these friendships. Yet parents have rarely been asked to report on the friendships and peer relationships of their autistic children. This study therefore sought to examine parents' perspectives on the friendships and social difficulties of their autistic daughters, and their views and concerns about their daughters' futures. Methods: Twenty parents of autistic adolescent girls, aged between 11 and 18 years, took part in semi-structured interviews on the topics of friendships, conflict and thoughts about adulthood and the future. Results: Results demonstrated that parents often have significant involvement in their daughters' social lives and friendships and have a range of views on these relationships. They highlighted both benefits and pitfalls of their daughters' peer interactions, and the perceived negative influence of these interactions on their daughters' mental health. Most parents had significant concerns about their daughters' futures, either about their ability to live independently, or their potential vulnerability to exploitation. Despite these concerns around sexual relationships, some parents were avoiding raising the issue with their daughters. Conclusions: Adolescent autistic girls often have positive, close friendships, but can also be the victims of bullying, with significant negative impacts on their mental health, at least according to their parents. Concerns about girls' development into adulthood were commonplace, with parents taking a range of approaches to attempt to talk about the future with their daughters. Implications: There is an urgent need for more open conversations to help autistic girls stay safe and secure as they mature, supporting their ability to understand and negotiate more intimate social relationships. Future research should examine these changing relationships as autistic girls' transition to adulthood and should seek to combine the views of parents alongside the young people themselves.